2019
DOI: 10.3390/jfb10020025
|View full text |Cite
|
Sign up to set email alerts
|

The Application of 29Si NMR Spectroscopy to the Analysis of Calcium Silicate-Based Cement using Biodentine™ as an Example

Abstract: Biodentine is one of the most successful and widely studied among the second generation of calcium silicate-based endodontic cements. Despite its popularity, the setting reactions of this cement system are not currently well understood. In particular, very little is known about the formation and structure of the major calcium silicate hydrate (C-S-H) gel phase, as it is difficult to obtain information on this poorly crystalline material by the traditional techniques of powder X-ray diffraction analysis (XRD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…Thus, this mixture makes it a better filling material, when compared to others such as Portland and MTA cement [8]. The hydration kinetics of these components in Biodentine™ has improved its physicochemical properties such as the mechanical strength, speed of curing, the initial and the final setting time [8,12,13]. Biodentine™ has been considered as a promising pulp capping material that can be used in the field of restorative dentistry to replace the dentine.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this mixture makes it a better filling material, when compared to others such as Portland and MTA cement [8]. The hydration kinetics of these components in Biodentine™ has improved its physicochemical properties such as the mechanical strength, speed of curing, the initial and the final setting time [8,12,13]. Biodentine™ has been considered as a promising pulp capping material that can be used in the field of restorative dentistry to replace the dentine.…”
Section: Introductionmentioning
confidence: 99%
“…Biodentine (Septodont, Saint-Maur-des-Fossés, France) is composed mostly of tricalcium silicate, zirconium oxide, and calcium carbonate powder, which are mixed with a supplied solution that includes calcium chloride [12,13]. The reduced setting time compared to MTA is achieved by diminishing the particle size and adding calcium chloride to expedite the reactions [13][14][15]. The substitution of bismuth oxide with zirconium oxide may also play a role in reduced setting time, because this component has been reported to expedite the primary hydration reaction [13].…”
Section: Introductionmentioning
confidence: 99%
“…The reduced setting time compared to MTA is achieved by diminishing the particle size and adding calcium chloride to expedite the reactions [13][14][15]. The substitution of bismuth oxide with zirconium oxide may also play a role in reduced setting time, because this component has been reported to expedite the primary hydration reaction [13]. Previous studies of this material's effects on dental pulp stem cells demonstrated its biocompatible ability, odontoblast differentiation ability, and mineralization potential [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous progress has been accomplished in last several decades in the field of materials science 1,2,3 . In dentistry, the concept of using inert materials for tissue repair has been replaced with strategy to find bioactive materials which positively interact with human tissues 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet clinical requirements of CSC based dental material, a radiopacifier has to be added to its composition to allow cement's visibility on radiographs 2,8,9 . However, finding an ideal balance between the ratio of radiopacifier and cement powder remains a challenge of the dental and engineering community 3,10,11 . When choosing a proper radiopacifier for cement fabrication several aspects should be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%